Predictive value of electrographic neonatal seizures for later epilepsy: A call for a broader perspective - Lucia Fusco (Epilepsia Open)
Abstract This is a letter to the editor commenting on a recently published study on electrographic seizures as predictors of epilepsy in neonates with encephalopathy. The letter highlights potential overemphasis on electrographic neonatal seizures, underscores the importance of severely abnormal EEG backgrounds and advanced neuroimaging, and suggests incorporating genetic analyses for a more comprehensive understanding.